Call for new criteria for monitoring and registering Natura 2000 species data - Meritxell Genovart; Roberto Salguero‐Gomez; Fernando Colchero; Francisco Guil; Joan Rabassa‐Juvanteny; Julia Uriach‐Dasca; Dalia Amor Conde; Jean Michel Gaillard; Tim Coulson (Conservation Biology, 2025)
The European Union's Birds and Habitats Directives are intended to guarantee the persistence of species and natural habitats across member states. To achieve this laudable aim, the Natura 2000 network of protected areas was established in 1992. Since then, member states are required to regularly monitor species and habitats and report findings to the European Commission, which requires substantial investment from all countries. The Natura 2000 network is an invaluable example of a large‐scale coordinated network developed to address major conservation issues. Based on our analysis of the 2020 Species Natura 2000 database and on expert opinions by Natura 2000 executives, we found that the network is failing to adequately show biodiversity status and guide conservation because it does not allow cross‐border comparisons of species’ and populations’ conservation status. The main contributing factor to this failure is that member states frequently fail to follow reporting EU guidelines, resulting in heterogeneity in criteria for monitoring and registering species among Natura 2000 areas. We advocate developing new unified and realistic criteria for monitoring and reporting species data that correctly allow cross‐border comparisons and conservation diagnosis. We propose that monitoring protocols and current criteria be modified slightly by considering species’ life‐history strategies, distribution, and conservation status. We do not suggest a major overhaul of the directives; rather, we propose debate on how relatively small changes in guidelines could improve the utility of the huge amount of data collected from the Natura 2000 network.

The diversity of population responses to environmental change - Fernando Colchero; Owen R. Jones; Dalia A. Conde; David Hodgson; Felix Zajitschek; Benedikt R. Schmidt; Aurelio F. Malo; Susan C. Alberts; Peter H. Becker; Sandra Bouwhuis; Anne M. Bronikowski; Kristel M. De Vleeschouwer; et al. (Ecology Letters, 2019)
The current extinction and climate change crises pressure us to predict population dynamics with ever‐greater accuracy. Although predictions rest on the well‐advanced theory of age‐structured populations, two key issues remain poorly explored. Specifically, how the age‐dependency in demographic rates and the year‐to‐year interactions between survival and fecundity affect stochastic population growth rates. We use inference, simulations and mathematical derivations to explore how environmental perturbations determine population growth rates for populations with different age‐specific demographic rates and when ages are reduced to stages. We find that stage‐ vs. age‐based models can produce markedly divergent stochastic population growth rates. The differences are most pronounced when there are survival‐fecundity‐trade‐offs, which reduce the variance in the population growth rate. Finally, the expected value and variance of the stochastic growth rates of populations with different age‐specific demographic rates can diverge to the extent that, while some populations may thrive, others will inevitably go extinct.

Two parthenogenetic populations of Chara canescens differ in their capacity to acclimate to irradiance and salinity - Ralf Schaible; Antje Gerloff-Elias; Fernando Colchero; Hendrik Schubert (Oecologia, 2012)

Understanding movement data and movement processes: current and emerging directions - Robert S. Schick; Scott R. Loarie; Fernando Colchero; Benjamin D. Best; Andre Boustany; Dalia A. Conde; Patrick N. Halpin; Lucas N. Joppa; Catherine M. McClellan; James S. Clark (Ecology Letters, 2008)
Animal movement has been the focus on much theoretical and empirical work in ecology over the last 25 years. By studying the causes and consequences of individual movement, ecologists have gained greater insight into the behavior of individuals and the spatial dynamics of populations at increasingly higher levels of organization. In particular, ecologists have focused on the interaction between individuals and their environment in an effort to understand future impacts from habitat loss and climate change. Tools to examine this interaction have included: fractal analysis, first passage time, Lévy flights, multi‐behavioral analysis, hidden markov models, and state‐space models. Concurrent with the development of movement models has been an increase in the sophistication and availability of hierarchical bayesian models. In this review we bring these two threads together by using hierarchical structures as a framework for reviewing individual models. We synthesize emerging themes in movement ecology, and propose a new hierarchical model for animal movement that builds on these emerging themes. This model moves away from traditional random walks, and instead focuses inference on how moving animals with complex behavior interact with their landscape and make choices about its suitability.